2019
DOI: 10.3389/fpsyg.2019.02102
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Attitudes to Female Body Shape in Spanish Women With High and Low Body Dissatisfaction

Abstract: Research on implicit attitudes to body image has grown substantially in recent years. The extant evidence reveals an implicit weight bias in the general population that has generally been interpreted in terms of anti-fat attitudes. However, research with the Implicit Relational Assessment Procedure (IRAP) shows that this bias appears to be driven by pro-slim rather than anti-fat implicit attitudes. Besides, the only IRAP study of this sort conducted in Spain found no evidence of such implicit weight bias (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 51 publications
5
21
0
1
Order By: Relevance
“…Participants in Maroto-Expósito et al [ 28 ] showed positive attitudes of similar magnitude both to pictures of underweight and pictures of overweight models. This pattern of results was replicated in a later study from the same research group [ 27 ], but only for participants with very low levels of body dissatisfaction. Participants with high levels of body dissatisfaction showed a preference for underweight model pictures similar to that found in the aforementioned studies by Roddy and colleagues [ 30 , 31 ] (i.e.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Participants in Maroto-Expósito et al [ 28 ] showed positive attitudes of similar magnitude both to pictures of underweight and pictures of overweight models. This pattern of results was replicated in a later study from the same research group [ 27 ], but only for participants with very low levels of body dissatisfaction. Participants with high levels of body dissatisfaction showed a preference for underweight model pictures similar to that found in the aforementioned studies by Roddy and colleagues [ 30 , 31 ] (i.e.…”
Section: Introductionsupporting
confidence: 52%
“…Some of them, with samples comprising both female and male participants [ 29 31 ] found an implicit weight bias (an overall evaluative preference for pictures of thin models over pictures of overweight models) that was entirely attributable to pro-thin attitudes and not to anti-fat ones (i.e., scores based on trials presenting overweight models were indicative of a neutral attitude). Other studies, with female-only samples [ 27 , 28 ] did not find any implicit bias. Participants in Maroto-Expósito et al [ 28 ] showed positive attitudes of similar magnitude both to pictures of underweight and pictures of overweight models.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…2. In line with the study of Hernández-López et al (2019), we assume a relation between implicit attitudes toward thinness and fatness and body satisfaction. 3.…”
Section: Main Goal Of This Studymentioning
confidence: 99%
“…The authors of this study did not find a relation between individual difference variables, like an appearance rating and an affective priming task, as well. The different results in the study of Hernández-López et al (2019) could again be attributed to the different methodology, first due to the application of the IRAP and second due to the investigation of women with extreme forms of body dissatisfaction only. Consequently, it is necessary to take the used implicit measurement into account when discussing about implicit attitudes toward body images.…”
Section: Implicit and Explicit Affective Attitudes Toward Under-and Overweightmentioning
confidence: 99%